Nacelle design for ultra-high bypass ratio engines with CFD based optimisation - Robinson, Matthew; MacManus, David G.; Christie, Robert; Sheaf, Christopher T.; Grech, Nicholas (Elsevier, 2020)
As the size of aero-engines has increased in recent years, the need for slimmer and shorter nacelles has become more pressing. A more aggressive design space must therefore be explored for nacelle designs which are expected to perform worse in the off design conditions such as spillage than current nacelle designs. In this work, a novel design space has been explored through the use of an optimisation method which evaluated nacelle aerodynamic performance based on computational fluid dynamics simulations. A multi-objective optimisation was undertaken where cruise drag, drag rise Mach number, spillage drag and two metrics based on the pressure distribution of the nacelle were optimised. Comparable optimal designs were picked from the Pareto sets of optimisations carried out at different nacelle lengths and radial offsets and some key outcomes established from their aerodynamics and geometries. It was determined that a reduction in the length of the nacelle from 3.8 highlight radii to 3.1 radii resulted in a significantly worse aerodynamic performance which included an increase in peak surface isentropic Mach number at cruise of 0.1 and up to four times as much spillage drag. It was however also established from the optimisation results that as the required drag rise Mach number was decreased the overall performance of short nacelles improved significantly.
Keywords: Optimisation; Nacelle; CFD; UHBPR